Pemberdayaan Kelompok Wanita Tani melalui Penguatan Kapasitas Pemasaran Digital Berbasis Komunitas di Daerah Sudiang Makassar - Adrianah Adrianah; Nur Apriyani; Ibrahim Syah; Husnul Khatimah Syarif (Jurnal Pengabdian Masyarakat Waradin, 2025)
This community service activity aims to empower the Women Farmers Group (KWT) in Sudiang, Makassar, through capacity building in digital marketing. In the era of rapidly developing digitalization and increasingly open and competitive markets, women farmers are required to be able to master digital technology-based marketing strategies so that the local agricultural products they produce can reach a wider market, not only at the local level but also regionally and even nationally. The methods used in this activity include interactive training, direct technical assistance, as well as social media development and the use of e-commerce platforms. Special training focuses on practical skills such as creating promotions, managing Instagram Business accounts, using WhatsApp Business content, and an introduction to the basics of branding and product photography. The assistance is carried out in stages to ensure that participants not only understand the material theoretically but also are able to implement it independently. The results of the activity show a significant increase in participants' understanding and skills in using digital technology as a product marketing tool. Participants become more confident in publishing their products online and are able to manage social media accounts professionally. One of the program's key achievements is the formation of a local digital community among women's groups (KWTs), which serves as a collaborative network for sharing information, marketing strategies, and supporting joint promotions. This community opens up opportunities for sustainable, long-term collaboration to collectively increase product sales value. Overall, this activity represents a strategic step in building women's economic independence through the inclusive and applicable use of digital technology. With this training, it is hoped that women's groups (KWTs) can become active actors in the local digital economy ecosystem and compete healthily in the open market.